2012
DOI: 10.1038/jhh.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

The associations between oxygen radical absorbance capacity of dietary intake and hypertension in type 2 diabetic patients

Abstract: The objective of this study was to investigate the potential associations between oxygen radical absorbance capacity (ORAC) of fruits, vegetables, legumes and nuts, and blood pressure in type 2 diabetic patients in Tehran. In a cross-sectional study of 506 type 2 diabetic patients, aged 28-75 years, usual dietary intakes were assessed by means of a 168-item food-frequency questionnaire. To calculate the estimated hydrophilic-ORAC, total ORAC, and total phenolics (TP) of fruits, vegetables, legumes and nuts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Among them, the oxygen radical absorption capacity (ORAC, classified as HAT) [1] has emerged as a test of choice in measuring the peroxyl radical scavenging capacity in foods and other matrices [15]. The correct use of the data obtained by this methodology through epidemiological clinical trials has broadened the knowledge about the dietary intake of antioxidants and their relationship with chronic diseases [16,17,18,19,20,21,22,23]. These epidemiological studies support the concept that food intake of ORAC (Oxygen Radical Absorbance Capacity) compounds above 10,000 µmol TE (Trolox equivalents) is related to a decreased risk or incidence of hypertension and cerebral infarction [1].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the oxygen radical absorption capacity (ORAC, classified as HAT) [1] has emerged as a test of choice in measuring the peroxyl radical scavenging capacity in foods and other matrices [15]. The correct use of the data obtained by this methodology through epidemiological clinical trials has broadened the knowledge about the dietary intake of antioxidants and their relationship with chronic diseases [16,17,18,19,20,21,22,23]. These epidemiological studies support the concept that food intake of ORAC (Oxygen Radical Absorbance Capacity) compounds above 10,000 µmol TE (Trolox equivalents) is related to a decreased risk or incidence of hypertension and cerebral infarction [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that ORAC from foods may have associations with preventing the development of human diseases. Dietary ORAC showed an inverse association with hypertension in type 2 diabetic patients in a cross-sectional study, suggesting that dietary antioxidants may decrease the risk of hypertension [26]. In particular, phenolic intake, based on the ORAC database, decreased the risk of endometrial cancer, revealing the role of antioxidants in preventing carcinogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
“…An assay of oxygen radical absorbance capacity (ORAC) has been proposed to provide a parameter reflecting antioxidant activities in foods, which describes the cumulative capacity of food components to scavenge free radicals, as well as other synergistic antioxidant effects related inflammatory complications [22][23][24][25]. Several epidemiological studies have shown the associations between total antioxidant capacity based on ORAC and health benefits, although the results were inconsistent depending on the type of disease [26][27][28]. However, no study has yet assessed the associations between dietary ORAC and CRC risk underlying the plasma IL-6 level, which is regarded as a tumor-promoting biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…The odds ratios of both systolic (>140 mm Hg) and diastolic blood pressure (>90 mm Hg) decreased across increasing quartiles of total dietary ORAC intake [47].…”
Section: Clinical and Epidemiology Studies: Dietary Antioxidant And Hmentioning
confidence: 91%